2015
DOI: 10.1007/s12110-015-9239-2
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Protection

Abstract: Pregnancy involves puzzling aversions to nutritious foods. Although studies generally support the hypotheses that such aversions are evolved mechanisms to protect the fetus from toxins and/or pathogens, other factors, such as resource scarcity and psychological distress, have not been investigated as often. In addition, many studies have focused on populations with high-quality diets and low infectious disease burden, conditions that diverge from the putative evolutionary environment favoring fetal protection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 51 publications
0
37
1
Order By: Relevance
“…Placek & Hagen (2015) also found that pathogen avoidance seemed to best explain avoidance of meat. This study did not systematically distinguish foods that were avoided due to aversive reactions versus those that were avoided due to advice from others, however (instead relying on mothers to make that distinction); did not determine from whom avoidances were learned; and its best-fitting exploratory model of meat aversions used number of household members as an index of pathogen exposure (McDade, Rutherford, Adair, & Kuzawa, 2009), which is an indirect measure at best.…”
Section: Study Goals and Predictionsmentioning
confidence: 91%
See 4 more Smart Citations
“…Placek & Hagen (2015) also found that pathogen avoidance seemed to best explain avoidance of meat. This study did not systematically distinguish foods that were avoided due to aversive reactions versus those that were avoided due to advice from others, however (instead relying on mothers to make that distinction); did not determine from whom avoidances were learned; and its best-fitting exploratory model of meat aversions used number of household members as an index of pathogen exposure (McDade, Rutherford, Adair, & Kuzawa, 2009), which is an indirect measure at best.…”
Section: Study Goals and Predictionsmentioning
confidence: 91%
“…Alternatively, because physiological cues of toxicity, such as bitterness and nausea, do not reliably indicate teratogenicity, women might have evolved to individually and socially learn associations between foods and poor pregnancy outcomes, independent of their own or others’ aversive reactions (Hagen, Roulette, & Sullivan, 2013; Placek & Hagen, 2015), consistent with generic cultural transmission models (e.g., Boyd & Richerson, 1985). Under this hypothesis, individual learners would know why they avoided a food, but might or might not transmit this reason to others (e.g., “do not eat papaya because it causes abortion” vs. “do not eat papaya.”).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations